2008
DOI: 10.1007/bf03175585
|View full text |Cite
|
Sign up to set email alerts
|

Molecular analysis of multidrug resistantMycobacterium tuberculosis isolates from Morocco

Abstract: Tuberculosis remains a global threat to public health. Considerable efforts have been made to combat this disease. However, the emergence of Mycobacterium tuberculosis (Mtb) strains resistant to the major anti-tuberculosis drugs especially multidrug resistant (MDR) strains poses a deadly threat to control programs. The present study aims to identify the most common mutations within multidrug-resistant M. tuberculosis Moroccan isolates in order to use them as molecular markers for early and rapid detection of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 31 publications
(42 reference statements)
1
7
0
Order By: Relevance
“…Among the 703 recruited strains, 90 cases were MDR (12.8%), which is in agreement with previously reported data in Morocco [ 3 , 25 ]. DNA genotyping showed that mutations in RRDR region of rpoB gene and, in katG gene and inhA promoter region, are the main SNPs conferring resistance to RIF and INH, respectively, confirming previously reported data [ 21 23 ] and reaffirming the usefulness of rpoB , katG and inhA promoter mutations as predictive markers for MDR TB. Moreover, molecular analysis could be limited to rpoB516, rpoB526, rpoB531, katG315 and inhA− 15 mutations, due to their high sensitivity and spectificity, to detect MDR strains.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Among the 703 recruited strains, 90 cases were MDR (12.8%), which is in agreement with previously reported data in Morocco [ 3 , 25 ]. DNA genotyping showed that mutations in RRDR region of rpoB gene and, in katG gene and inhA promoter region, are the main SNPs conferring resistance to RIF and INH, respectively, confirming previously reported data [ 21 23 ] and reaffirming the usefulness of rpoB , katG and inhA promoter mutations as predictive markers for MDR TB. Moreover, molecular analysis could be limited to rpoB516, rpoB526, rpoB531, katG315 and inhA− 15 mutations, due to their high sensitivity and spectificity, to detect MDR strains.…”
Section: Discussionsupporting
confidence: 87%
“…It is widely accepted that the knowledge of the Mycobacterium tuberculosis (MTB) resistance spectrum is important for the effective treatment of MDR- and XDR-TB. In Morocco, many studies have already investigated first line drug resistance prevalence and associated genetic mutations [ 21 24 ]. However, to our best knowledge, no study has explored the pre-XDR and XDR TB status in Morocco.…”
Section: Discussionmentioning
confidence: 99%
“…Early detection of MDR-TB is crucial both for the patient management and infection control in TB positive cases [38] . Increased prevalence of drug resistant tuberculosis in Bangladesh and other developing countries is a growing threat to tuberculosis control since a few drugs has so far been found to be effective against TB [3] , [4] , [8] , [38] , [39] , [40] , [41] , [42] , [43] . According to the WHO report in 2010, the estimated MDR-TB among the notified retreatment cases (n = 7795) was 2200 (28%) [44] .…”
Section: Discussionmentioning
confidence: 99%
“…Samples were cultured on Lowenstein-Jensen media at the regional TB laboratory or the National TB Reference Laboratory (LNRT). Drug susceptibility testing (DST) for isoniazid (H), rifampin (R), ethambutol (E) and streptomycin (S) was performed on all positive cultures at LNRT as previously described [16] . Culture data from one city did not meet quality control standards and were excluded from final analyses.…”
Section: Study Population and Methodsmentioning
confidence: 99%